11C-Acetate Positron Emission Tomography for Detection of Occult Metastatic Recurrence in Hepatoblastoma. Issue 4 (May 2016) - Liu, Anthony Pak-Yin; Wong, Ka-Nin; See, Queenie Wing-Shan; Chan, Godfrey Chi-Fung; Chiang, Alan Kwok-Shing
Abstract : Hepatoblastoma is the most common primary liver cancer in the pediatric population. Disease relapse might be occult and difficult to detect. 11 C-acetate positron emission tomography has been applied in patients with hepatocellular carcinoma due to the insensitivity of 18 fluorodeoxyglucose, but data on hepatoblastoma patients have been scarce. We describe the use of 11 C-acetate positron emission tomography/computed tomography scan as a sensitive method in the identification of an occult bony metastatic recurrence in a 6-year-old girl with a history of hepatoblastoma treated with chemotherapy.